Non‐alcoholic fatty liver disease comorbid with major depressive disorder: The pathological features and poor therapeutic efficacy. Issue 6 (June 2015) - Tomeno, Wataru; Kawashima, Keigo; Yoneda, Masato; Saito, Satoru; Ogawa, Yuji; Honda, Yasushi; Kessoku, Takaomi; Imajo, Kento; Mawatari, Hironori; Fujita, Koji; Saito, Satoru; Hirayasu, Yoshio; et al.
Abstract Background and Aim Major depressive disorder (MDD) is an important public health problem, and it is often comorbid with many chronic diseases. The purpose of this study was to identify the clinical features of non‐alcoholic fatty liver disease (NAFLD) patients comorbid with MDD and to investigate the influence of MDD on the effect of treatment in patients with NAFLD. Methods A total of 258 patients with biopsy‐proven NAFLD were included. MDD was diagnosed according to the criteria of the Diagnostic and Statistical Manual of Mental Disorders, 4th edition, text revision. The patients were followed up for 48 weeks under standard care for NAFLD, which consisted mainly of lifestyle modification. Results There were 32 patients comorbid with MDD. They were characterized by more severe histological steatosis and higher NAFLD activity score, and also significantly higher levels of serum aminotransferase, γ‐glutamyl transpeptidase and ferritin, than age‐and‐sex‐matched NAFLD patients without MDD. Moreover, NAFLD patients with MDD showed poor response to the standard care for NAFLD, in body weight loss and in other parameters. Particularly, NAFLD patients with unstable MDD (not in full/partial remission) showed severe resistance to the treatment. Conclusion This is the first study to demonstrate the clinical features and response to therapy of NAFLD patients comorbid with MDD. The comorbid state of MDD was associated with more severe histological liver steatosis and worse treatment outcomes in patients with NAFLD. Further investigations are required to develop new lifestyle modification programs that enable NAFLD patients with MDD to achieve the treatment goal.